Statistical Assessment Of Unemployment And Its Causes In Tashkent Region (Progress Annals: Journal of Progressive Research, 2025)
Today in our Republic, the development of the labor market and its regulation, taking into account the needs of the modern labor market, requires the development of the most effective system for training highly qualified personnel and training everyone. round competitive specialists. In addition, determining the place of young specialists in production and increasing their competitiveness with specialists from foreign countries is one of the most important issues today. Based on the above objectives, as a result of creating new jobs and supporting the orientation of young people towards entrepreneurship, consistent systematic work is being carried out to achieve the well-being of the population, especially those in need of social protection.